Conversational Implicature in Tim Burton’s Netflix Series “Wednesday” - Fadillah Ayu Natasya; Sukardi Weda; Murni Mahmud (State University of Makassar, 2026)
This study examines the use of conversational implicature in the Netflix series by Tim Burton,